Pengaruh Model Pembelajaran Tematik dan Gaya Belajar Terhadap Hasil Belajar Siswa Kelas II - Husen Husen (Reforma : Jurnal Pendidikan dan Pembelajaran, 2017)
Thematic learning model is a learning model that students pay attention to SD/MI that frame of mind is still intact, and the understanding of the concept are through the real world and based to the students lives. In this study the researcher focus to the model of learning interaction and learning styles on learning outcomes. The researcher used experimental study. The study population was all students in second student grade. The sample amounted to 90 students from both MI, it means that the researcher used purposive sampling, where all students are included on certain conditions. The collected data were statistically processed using the techniques of inferential analysis of variance (Anova) two-factor 2 x 2. The results of this study, (1) there are differences in learning outcomes between students who use thematic learning and conventional learning, (2) there are differences in student learning outcomes that have a stylish visual, auditory and kinesthetic, and (3) there is no interaction between learning models and styles learning on learning outcomes. Descriptive Statistics show that the application of thematic learning (mean 80.49) and the conventional learning (mean 77.87). And mean learning outcomes based on visual learning style is 84.81, auditory learning style is 73.48, and kinesthetic learning styles is 75.09. Based on the research findings, it is recommended to the elementary school teachers to apply the thematic instructional strategies in the instruction to improve student learning achievement. The characteristic of thematic strategy can empower student to learn optimally and support the student learning achievement.Keywords: Thematic Learning Model, Learning Styles and Student Learning Outcomes